Concrete admixtures and their preparation methods
By melting the basalt fibers with fly ash and oxidizing the surface, and applying composite functional agents to the surface, the problem of basalt fibers agglomeration in concrete is solved, and the compressive strength and flexural strength of the concrete are significantly improved, achieving better results dispersibility and mechanical properties.
Patent Information
- Application Number
- CN202411449295.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The agglomeration problem of basalt fibers in concrete leads to poor dispersion, affecting compressive strength and flexural strength.
By crushing the basalt fibers and heating and melting with fly ash, brushed with platinum-rhodium alloy leak plates, then surface oxidized in hydrogen peroxide, and coating the surface with composite functional agent to form a concrete blend with good dispersion.
The compressive strength and flexural strength of concrete are significantly improved, ensuring the good dispersion of basalt fibers in concrete, and improving the mechanical properties of building materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite materials, and in particular, relates to a concrete admixture and a preparation method thereof. Background Art
[0002] With the rapid development of the construction industry and the continuous improvement of engineering quality, the requirements for concrete performance are becoming increasingly stringent. In order to meet the requirements of buildings in terms of mechanical properties, durability and construction quality, people often add concrete admixtures when preparing concrete. As an important means to improve the performance of concrete, the use of concrete admixtures can be traced back to the 1950s and 1960s, when people mainly replaced part of the cement by adding a certain amount of admixtures to concrete to reduce material costs. In the 1970s and 1980s, with the deepening of the understanding of admixture performance, admixtures began to be widely used in water conservancy projects and large buildings to improve the hydration heat performance of concrete and reduce temperature cracks. After entering the 1990s, the research and application of admixtures have made breakthrough progress. Industrial waste slag and other wastes have been used as concrete admixtures in large quantities, which not only improves the performance of concrete, but also realizes the recycling of resources. Concrete admixtures can be divided into active admixtures and inactive admixtures according to their activity. Active admixtures, such as fly ash, granulated blast furnace slag powder, silica fume, etc., can react with calcium hydroxide generated by cement hydration to generate hydration products with gelling ability, thereby improving the strength and durability of concrete. Inactive admixtures, such as basalt fiber, mainly play a filling role. Although they do not directly react with cement components, they can also improve the performance of concrete to a certain extent.
[0003] Basalt fiber is a continuous fiber made from natural basalt ore by high-temperature melting and rapid drawing. This fiber has high strength, high modulus, excellent corrosion resistance and anti-aging properties, and also has lighter weight, better corrosion resistance and non-magnetic properties. In addition, the production process of basalt fiber is environmentally friendly and does not produce harmful substances. It is a green and environmentally friendly material. By adding basalt fiber to concrete, the tensile strength, flexural strength and splitting strength of concrete can be significantly improved. It has been widely used in bridges, tunnels, high-rise buildings, water conservancy projects and other fields. However, basalt fiber also has the problem of smooth surface and easy agglomeration, so its dispersion in concrete is not good, which will lead to different internal components of the cured cement mortar and affect the internal compressive strength. How to solve the agglomeration problem of basalt fiber in concrete is an urgent problem to be solved in the existing technology. Summary of the invention
[0004] The object of the present invention is to provide a concrete admixture and a preparation method thereof, so as to solve the problems mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] Concrete admixture, including the following raw materials in parts by weight: 75-85 parts of basalt, 10-20 parts of fly ash, and 3-5 parts of composite functional agent;
[0007] The method for preparing a concrete admixture comprises the following steps:
[0008] Step 1: Weigh each raw material by mass, crush the basalt fiber, sieve it to remove impurities, and put it into the basalt electric melting furnace together with fly ash, and heat it until it melts to obtain a molten liquid;
[0009] Step 2: The molten liquid obtained in the first step is drawn through a platinum-rhodium alloy bushing to obtain basalt fiber;
[0010] Step 3: soaking the basalt fiber obtained in the second step in a hydrogen peroxide solution for surface oxidation, washing with deionized water after the reaction is completed, transferring to an oven for drying to obtain surface oxidized basalt fiber;
[0011] Step 4: uniformly coating the composite functional agent on the surface of the oxidized basalt fiber, and after standing for 1 hour, transferring the basalt fiber coated with the composite functional agent to an oven and drying to constant weight to obtain the concrete admixture.
[0012] Furthermore, the sieve used for sieving in the first step is a 400-mesh sieve.
[0013] Furthermore, the temperature of heating and melting in the first step is 1500-1650°C.
[0014] Furthermore, the temperature of the melt drawing in the second step is 1240-1290°C.
[0015] Furthermore, the hydrogen peroxide used in the third step is a 5% by mass hydrogen peroxide solution.
[0016] Furthermore, in the third step, the soaking temperature is 40-45°C, and the oven is set at 60°C.
[0017] Furthermore, in the fourth step, the standing temperature condition is 45°C and the oven setting temperature is 60°C.
[0018] Furthermore, the composite functional agent is prepared by the following steps:
[0019] Step 1: 3-aminopropyltriethoxysilane, phthalic anhydride, tetrabutylammonium bromide and tetrahydrofuran were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at a temperature of 110-125° C. for 12-14 hours. After the reaction was completed, ether was added to the three-necked flask, vacuum filtered, and the obtained solid was recrystallized to obtain intermediate 1;
[0020] The reaction process is as follows:
[0021]
[0022] Step 2: Mix the intermediate 1, 2-chloromethylacrylic acid and acetonitrile in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 20-30°C for 20-24h. After the reaction is completed, rotary evaporation is performed to obtain the intermediate 2;
[0023] The reaction process is as follows:
[0024]
[0025] Step 3: Mix the intermediate 2, p-hydroxybenzenesulfonic acid, concentrated sulfuric acid and dimethyl sulfoxide in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 60-80°C for 8-10 hours. After the reaction is completed, cool to room temperature and wash with a saturated sodium carbonate solution. Separate the organic layer with a separatory funnel and then rotary evaporate to obtain the composite functional agent;
[0026] The reaction process is as follows:
[0027]
[0028] Furthermore, the amount ratio of 3-aminopropyltriethoxysilane, phthalic anhydride, tetrabutylammonium bromide and tetrahydrofuran used in step 1 is 0.1 mol: 0.1-0.12 mol: 6-10 g: 80-120 mL.
[0029] Furthermore, the amount ratio of the intermediate 1, 2-chloromethylacrylic acid and acetonitrile used in step 2 is 0.08 mol: 0.08-0.1 mol: 60-80 mL.
[0030] Furthermore, the concentrated sulfuric acid used in step 3 is concentrated sulfuric acid with a mass fraction of 98%, and the amount ratio of the intermediate 2, p-hydroxybenzenesulfonic acid, concentrated sulfuric acid, and dimethyl sulfoxide used is 0.05 mol: 0.05-0.08 mol: 10-14 g: 80-100 mL.
[0031] Beneficial effects of the present invention:
[0032] 1) The present invention uses basalt, fly ash and composite functional agent as raw materials to prepare a concrete admixture; the present invention heats and melts the crushed basalt and fly ash together to obtain a molten liquid to enhance the roughness of the surface of the basalt fiber, then draws and forms the basalt fiber through a platinum-rhodium alloy plate, oxidizes the obtained basalt fiber with hydrogen peroxide and then dries it to enhance the hydroxyl activity of the surface of the basalt fiber, and finally coats the surface of the oxidized basalt fiber with a composite functional agent to obtain a concrete admixture. The preparation method of the concrete admixture of the present invention is simple, the obtained basalt fiber has good toughness, strong dispersibility in concrete, and can greatly improve the compressive strength and flexural strength of the concrete.
[0033] 2) The present invention uses 3-aminopropyltriethoxysilane and phthalic anhydride as raw materials and tetrabutylammonium bromide as a phase transfer catalyst, and obtains intermediate 1 through an amidation reaction between an amino group and a cyclic acid anhydride, and then causes the tertiary amine structure of intermediate 2 to react with the chlorine atom of 2-chloromethylacrylic acid to react with a quaternary ammonium salt to obtain intermediate 2, and finally causes the carboxyl group of intermediate 2 to react with the phenolic hydroxyl group of p-hydroxybenzenesulfonic acid to react with an esterification reaction, thereby obtaining a composite functional agent for modifying basalt fiber; the organic silicon structure of the composite functional agent of the present invention can react chemically with the hydroxyl group on the surface of the basalt fiber activated by hydrogen peroxide to form a molecular bridge for tight bonding, the quaternary ammonium salt structure of the composite functional agent is hydrophilic and can improve the dispersibility of the basalt fiber in concrete, and the composite functional agent also has a sulfonic acid group on its surface, which can adsorb cement particles and generate electrostatic repulsion on the surface, thereby improving the dispersibility of the basalt fiber in concrete, and the two are combined with each other and act synergistically, so that the concrete admixture finally obtained has good dispersibility in concrete and can greatly improve the compressive strength and flexural strength of concrete. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] A composite functional agent is prepared by the following steps:
[0037] Step 1: 0.1 mol 3-aminopropyltriethoxysilane, 0.1 mol phthalic anhydride, 6 g tetrabutylammonium bromide and 80 mL tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 110° C. for 12 h. After the reaction was completed, ether was added to the container, vacuum filtered, and the obtained solid was recrystallized to obtain intermediate 1;
[0038] Step 2: 0.08 mol of intermediate 1, 0.08 mol of 2-chloromethylacrylic acid and 60 mL of acetonitrile were mixed in a container, stirred evenly, and reacted at 20°C for 20 h. After the reaction was completed, intermediate 2 was obtained by rotary evaporation;
[0039] Step 3: 0.05 mol of intermediate 2, 0.05 mol of p-hydroxybenzenesulfonic acid, 10 g of 98% concentrated sulfuric acid, and 80 mL of dimethyl sulfoxide were mixed in a container, stirred evenly, and reacted at 60° C. for 8 h. After the reaction, cooled to room temperature and washed with a saturated sodium carbonate solution, the organic layer was separated and rotary evaporated to obtain the composite functional agent.
[0040] Example 2
[0041] A composite functional agent is prepared by the following steps:
[0042] Step 1: 0.1 mol 3-aminopropyltriethoxysilane, 0.11 mol phthalic anhydride, 8 g tetrabutylammonium bromide and 100 mL tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 118° C. for 13 h. After the reaction was completed, ether was added to the container, vacuum filtered, and the obtained solid was recrystallized to obtain intermediate 1;
[0043] Step 2: 0.08 mol of intermediate 1, 0.09 mol of 2-chloromethylacrylic acid and 70 mL of acetonitrile were mixed in a container, stirred evenly, and reacted at 25°C for 22 hours. After the reaction was completed, intermediate 2 was obtained by rotary evaporation;
[0044] Step 3: 0.05 mol of intermediate 2, 0.06 mol of p-hydroxybenzenesulfonic acid, 12 g of 98% concentrated sulfuric acid, and 90 mL of dimethyl sulfoxide were mixed in a container, stirred evenly, and reacted at 70° C. for 9 h. After the reaction, the mixture was cooled to room temperature and washed with a saturated sodium carbonate solution. The organic layer was separated and rotary evaporated to obtain the composite functional agent.
[0045] Example 3
[0046] A composite functional agent is prepared by the following steps:
[0047] Step 1: 0.1 mol 3-aminopropyltriethoxysilane, 0.12 mol phthalic anhydride, 10 g tetrabutylammonium bromide and 120 mL tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 125° C. for 14 h. After the reaction was completed, ether was added to the container, vacuum filtered, and the obtained solid was recrystallized to obtain intermediate 1;
[0048] Step 2: 0.08 mol of intermediate 1, 0.1 mol of 2-chloromethylacrylic acid and 80 mL of acetonitrile were mixed in a container, stirred evenly, and reacted at 30°C for 24 hours. After the reaction was completed, intermediate 2 was obtained by rotary evaporation;
[0049] Step 3: 0.05 mol of intermediate 2, 0.08 mol of p-hydroxybenzenesulfonic acid, 14 g of 98% concentrated sulfuric acid, and 100 mL of dimethyl sulfoxide were mixed in a container, stirred evenly, and reacted at 80° C. for 10 h. After the reaction, the mixture was cooled to room temperature and washed with a saturated sodium carbonate solution. The organic layer was separated and rotary evaporated to obtain the composite functional agent.
[0050] Example 4
[0051] Concrete admixture, comprising the following raw materials in parts by weight: 75 parts of basalt, 20 parts of fly ash, and 5 parts of the composite functional agent obtained in Example 1;
[0052] The method for preparing a concrete admixture comprises the following steps:
[0053] Step 1: Weigh each raw material by mass, crush the basalt fiber, sieve it through a 400-mesh screen to remove impurities, and put it into a basalt electric melting furnace together with fly ash, and heat it to 1500°C to melt and obtain a molten liquid;
[0054] Step 2: The molten liquid obtained in the first step is drawn through a platinum-rhodium alloy bushing at a temperature of 1240° C. to obtain basalt fiber;
[0055] Step 3: The basalt fiber obtained in the second step is immersed in a 5% by mass hydrogen peroxide solution at a temperature of 40°C for surface oxidation. After the reaction is completed, it is washed with deionized water and dried in an oven at 60°C to obtain surface oxidized basalt fiber.
[0056] Step 4: The composite functional agent obtained in Example 1 is uniformly coated on the surface of the oxidized basalt fiber. After standing at 45°C for 1 hour, the basalt fiber coated with the composite functional agent is transferred to an oven at 60°C and dried to constant weight to obtain the concrete admixture.
[0057] Example 5
[0058] Concrete admixture, comprising the following raw materials in parts by weight: 85 parts of basalt, 12 parts of fly ash, and 3 parts of the composite functional agent obtained in Example 2;
[0059] The method for preparing a concrete admixture comprises the following steps:
[0060] Step 1: Weigh each raw material by mass, crush the basalt fiber, sieve it through a 400-mesh screen to remove impurities, and then put it into a basalt electric melting furnace together with fly ash, and heat it to 1575℃ to melt and obtain a molten liquid;
[0061] Step 2: The molten liquid obtained in the first step is drawn through a platinum-rhodium alloy bushing at a temperature of 1265° C. to obtain basalt fiber;
[0062] Step 3: The basalt fiber obtained in the second step is immersed in a 5% by mass hydrogen peroxide solution at a temperature of 42°C for surface oxidation. After the reaction is completed, it is washed with deionized water and dried in an oven at 60°C to obtain surface oxidized basalt fiber.
[0063] Step 4: The composite functional agent obtained in Example 2 is uniformly coated on the surface of the oxidized basalt fiber. After standing at a temperature of 45°C for 1 hour, the basalt fiber coated with the composite functional agent is transferred to an oven at 60°C and dried to constant weight to obtain the concrete admixture.
[0064] Example 6
[0065] Concrete admixture, comprising the following raw materials in parts by weight: 80 parts of basalt, 16 parts of fly ash, and 4 parts of the composite functional agent obtained in Example 3;
[0066] The method for preparing a concrete admixture comprises the following steps:
[0067] Step 1: Weigh each raw material by mass, crush the basalt fiber, sieve it through a 400-mesh screen to remove impurities, and then put it into a basalt electric melting furnace together with fly ash, and heat it to 1650°C to melt and obtain a molten liquid;
[0068] Step 2: The molten liquid obtained in the first step is drawn through a platinum-rhodium alloy bushing at a temperature of 1290° C. to obtain basalt fiber;
[0069] Step 3: The basalt fiber obtained in the second step is immersed in a 5% by mass hydrogen peroxide solution at a temperature of 45°C for surface oxidation. After the reaction is completed, it is washed with deionized water and dried in an oven at 60°C to obtain surface oxidized basalt fiber;
[0070] Step 4: The composite functional agent obtained in Example 3 is uniformly coated on the surface of the oxidized basalt fiber. After standing at 45°C for 1 hour, the basalt fiber coated with the composite functional agent is transferred to an oven at 60°C and dried to constant weight to obtain the concrete admixture.
[0071] Comparative Example 1
[0072] The "composite functional agent in Example 3" used in Example 6 was removed, and the remaining formulas and steps remained unchanged.
[0073] According to the national standard GB / T 19139-2012 oil well cement test method, blank cement slurry and cement slurry with the concrete admixtures in Examples 4-6 and Comparative Example 1 added at a solid content of 1.5% were prepared, and the above cement slurries were poured into a mold for curing and curing. After curing at 80°C for 24 hours, the sample was demoulded to obtain cement stone, and then the cement stone was placed in a constant temperature water bath at 80°C for further curing for 2 days. The cement stone core was extracted to test the dispersibility of the concrete admixture in the cement slurry, and the compressive strength of the cement sand was tested. The test results are shown in Table 1:
[0074]
[0075] It can be seen from Table 1 that adding the concrete admixture of the present invention can effectively improve the compressive strength and flexural strength of cement after solidification. The concrete admixture using the composite functional agent of the present invention in the preparation process has better dispersibility and can better improve the compressive strength and flexural strength of cement after solidification. The concrete admixture without using the composite functional agent of the present invention in the preparation process will still agglomerate when mixed with cement slurry, so the dispersibility is not good. In summary, the concrete admixture of the present invention can effectively improve the compressive strength and flexural strength of cement after solidification, and can be widely used in the construction field.
[0076] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A concrete admixture, characterized in that: The raw materials include the following parts by weight: 75-85 parts of basalt, 10-20 parts of fly ash, and 3-5 parts of composite functional agent; Wherein, the composite functional agent is prepared by the following steps: Step 1: 3-aminopropyltriethoxysilane, phthalic anhydride, tetrabutylammonium bromide and tetrahydrofuran are mixed in a container, stirred evenly, and reacted at a temperature of 110-125° C. for 12-14 hours to obtain intermediate 1; Step 2: Mix the intermediate 1, 2-chloromethylacrylic acid and acetonitrile in a container, stir evenly, and react at 20-30° C. for 20-24 hours to obtain the intermediate 2; Step 3: Mix the intermediate 2, p-hydroxybenzenesulfonic acid, concentrated sulfuric acid and dimethyl sulfoxide in a container, stir evenly, and react at 60-80° C. for 8-10 hours to obtain the composite functional agent.
2. The concrete admixture according to claim 1, characterized in that: The amount ratio of 3-aminopropyltriethoxysilane, phthalic anhydride, tetrabutylammonium bromide and tetrahydrofuran used in step 1 is 0.1 mol: 0.1-0.12 mol: 6-10 g: 80-120 mL.
3. The concrete admixture according to claim 1, characterized in that: The amount ratio of the intermediate 1, 2-chloromethylacrylic acid and acetonitrile used in step 2 is 0.08 mol: 0.08-0.1 mol: 60-80 mL.
4. The concrete admixture according to claim 1, characterized in that: The concentrated sulfuric acid used in step 3 is concentrated sulfuric acid with a mass fraction of 98%, and the amount ratio of the intermediate 2, p-hydroxybenzenesulfonic acid, concentrated sulfuric acid, and dimethyl sulfoxide is 0.05 mol: 0.05-0.08 mol: 10-14 g: 80-100 mL.
5. The method for preparing a concrete admixture according to claim 1, characterized in that: The following steps are involved: Step 1: weigh 75-85 parts of basalt, 10-20 parts of fly ash, and 3-5 parts of composite functional agent according to their mass proportions, crush the basalt, sieve out impurities, and put it into a basalt electric melting furnace together with the fly ash, and heat it until it melts to obtain a molten liquid; Step 2: The molten liquid obtained in the first step is drawn through a platinum-rhodium alloy bushing to obtain basalt fiber; Step 3: soaking the basalt fiber obtained in the second step in a hydrogen peroxide solution for surface oxidation, washing with deionized water after the reaction is completed, transferring to an oven for drying to obtain surface oxidized basalt fiber; Step 4: uniformly coating the composite functional agent on the surface of the oxidized basalt fiber, and after standing for 1 hour, transferring the basalt fiber coated with the composite functional agent to an oven and drying to constant weight to obtain the concrete admixture.
6. The method for preparing a concrete admixture according to claim 5, characterized in that: The screen used for sieving in the first step is a 400 mesh screen.
7. The method for preparing a concrete admixture according to claim 5, characterized in that: The heating and melting temperature in the first step is 1500-1650°C.
8. The method for preparing a concrete admixture according to claim 5, characterized in that: The temperature of the melt drawing in the second step is 1240-1290°C.
9. The method for preparing a concrete admixture according to claim 5, characterized in that: The hydrogen peroxide used in the third step is a 5% by mass hydrogen peroxide solution, the soaking temperature is 40-45°C, and the oven temperature is set at 60°C.
10. The method for preparing a concrete admixture according to claim 5, characterized in that: In the fourth step, the temperature condition for standing still is 45°C and the temperature set in the oven is 60°C.
